PENGEMBANGAN MEDIA PEMBELAJARAN BERBANTU CANVA PADA MATERI KEBERAGAMAN BUDAYA INDONESIA UNTUK SISWA KELAS V SEKOLAH DASAR - Emilia Putri; Zaka Hadikusuma Ramadan (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
The aim of the research is to determine the development of Canva-assisted learning media on Indonesian cultural diversity material for fifth grade elementary school students and to determine the validity of the Canva-assisted learning media that has been created. The methodology used is R&D with the ADDIE development model. The development target is 21 students, 10 of whom are 2 material experts, 2 language experts, and 2 media experts. The research instruments used were material validation questionnaires, language validation questionnaires, media validation questionnaires and teacher response questionnaires and student response questionnaires. The research results obtained material validation of 94.06% in the "Very Valid" category. Language validation is 96.87% with the "Very Valid" category. Media validation is 97.18% in the "Very Valid" category. Overall, the validity of Canva-assisted learning media obtained an average score of 96.03% so that Canva-assisted learning media was categorized as very valid without revision and suitable for use. The teacher response results were 100% in the "Very positive" category. The results of 100% of student responses were in the "Very Positive" category. Based on research data, it shows that the Canva-assisted learning media developed is very suitable for use in Pancasila education subjects on Indonesian cultural diversity material for fifth grade elementary school students.